Confidence, Anxiety, and Peak Performance of Football Athletes at Safin Pati - Anggit Tinovega; Mohamad Annas (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This research is motivated by the importance of psychological actors in determining the peak performance of football athletes, especially confidence and anxiety. The purpose of this study is to analyze the relationship between confidence and anxiety levels on athletes' peak performance at Safin Pati Sports School. The research uses a quantitative approach with a correlational method. The research sample amounted to 40 athletes who were selected purposively. The instruments used were questionnaires to measure confidence, anxiety, and peak performance, with data analysis using descriptive statistics, normality tests, linearity, multicollinearity, and simple and multiple correlations. The results showed that self-confidence had a positive and significant relationship with peak performance (r = 0.662; p < 0.05), while anxiety also showed a significant relationship (r = 0.798; p < 0.05). Simultaneously, confidence and anxiety had a synonymous effect on peak performance with a contribution of 67.4%. The conclusion of this study is that increasing confidence and optimal anxiety management play an important role in supporting the achievement of peak performance of football athletes.